The Roles of Coenzyme A Binding Pocket Residues in Short and Medium Chain Acyl-CoA Synthetases - Yu Meng; Cheryl Ingram-Smith; Oly Ahmed; Kerry Smith (Life, 2023)
Short- and medium-chain acyl-CoA synthetases catalyze similar two-step reactions in which acyl substrate and ATP bind to form an enzyme-bound acyl-adenylate, then CoA binds for formation of the acyl-CoA product. We investigated the roles of active site residues in CoA binding in acetyl-CoA synthetase (Acs) and a medium-chain acyl-CoA synthetase (Macs) that uses 2-methylbutyryl-CoA. Three highly conserved residues, Arg193, Arg528, and Arg586 of Methanothermobacter thermautotrophicus Acs (AcsMt), are predicted to form important interactions with the 5′- and 3′-phosphate groups of CoA. Kinetic characterization of AcsMt variants altered at each of these positions indicates these Arg residues play a critical role in CoA binding and catalysis. The predicted CoA binding site of Methanosarcina acetivorans Macs (MacsMa) is structurally more closely related to that of 4-chlorobenzoate:coenzyme A ligase (CBAL) than Acs. Alteration of MacsMa residues Tyr460, Arg490, Tyr525, and Tyr527, which correspond to CoA binding pocket residues in CBAL, strongly affected CoA binding and catalysis without substantially affecting acyl-adenylate formation. Both enzymes discriminate between 3′-dephospho-CoA and CoA, indicating interaction between the enzyme and the 3′-phosphate group is important. Alteration of MacsMa residues Lys461 and Lys519, located at positions equivalent to AcsMt Arg528 and Arg586, respectively, had only a moderate effect on CoA binding and catalysis. Overall, our results indicate the active site architecture in AcsMt and MacsMa differs even though these enzymes catalyze mechanistically similar reactions. The significance of this study is that we have delineated the active site architecture with respect to CoA binding and catalysis in this important enzyme superfamily.